PROBLEMATIKA PENERAPAN PIDANA MATI DALAM KONTEKS PENEGAKAN HUKUM DI INDONESIA - Slamet Tri Wahyudi (Jurnal Hukum dan Peradilan, 2012)
Law enforcement without direction and not based on the three pillars of the justice of law, legal certainty and the benefits to society can break the law anyway even violate human rights. As one of the policies of the government that are not considered mencerminakan the values of justice and disturbing for the people, the government policy that acts of omission or delay in the application of the death penalty. This research is a normative legal normative juridical approach. The data collected is secondary data were analyzed using qualitative methods juridical analysis. Based on these results it can be concluded that in the application of the death penalty there are serious legal issues, this is due to government policies that commit omission or delay in the execution of the death penalty is a violation of human rights as stipulated in Article 28 of the 1945 Constitution. Keywords: Death penalty, Justice, Legal Certainty, Law